Assessment of Genetic Variability among Six Bangladeshi Foxtail Millet (Setaria italica L.) Varieties using RAPD Markers (Plant Tissue Culture and Biotechnology, 2026)
Foxtail millet (Setaria italica L.) is an ancient cereal crop known for its nutritional and medicinal benefits and for being highly adaptable to arid and semi-arid environments. Six varieties of foxtail millet were collected from Bangladesh Agricultural Research Institute (BARI) and different regions of Bangladesh for the assessment of their genetic variability employing Random Amplified Polymorphic DNA (RAPD) markers. This study generated a distinct genetic variability for the varieties, generating 299 bands with the fifteen RAPD primers of size range of 210 bp to 3000 bp with an average polymorphism rate of 97.06%. Among the six varieties, V2 (BARI Kaon-2) was found to be the most polymorphic with 98.75%, and V1 (BARI Kaon-1) was the least polymorphic with 91.66%. The cluster and dendrogram analyses further classified the varieties into distinct groups based on their genetic relationships. The genetic distance across the varieties ranged from 0.1865 to 0.9146. The closest relationship was observed between V5 (Local Variety-Manikganj) and V6 (Local Variety-Bhola), whereas V3 (BARI Kaon-3) and V4 (BARI Kaon-4) were found to be the most genetically distinct. The findings of the present study emphasize the effectiveness of RAPD markers for identifying genetic variation and provide significant information for future foxtail millet breeding programs that supports sustainable agriculture systems.Plant Tissue Cult. & Biotech. 36(1): 189-198, 2026 (June)